Public Discourse, Framing, and the Impact of the BDS Movement on EU-Israeli Economic Cooperation - Stolbunsky, Aleksandra; Weinfurter, Jaroslav; Šitera, Daniel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores the impact of the Boycott, Divestment, Sanctions (BDS) movement on EU–Israeli trade relations through a comparative analysis of the Czech Republic and the Netherlands. Using framing theory, rational choice theory, and the discourse-historical approach (DHA), it examines how public discourse, media narratives, and economic behavior interact. Survey data and media analysis reveal that while BDS framing resonates within certain activist circles, it fails to achieve broad public consensus or influence state policy. Trade data shows continued growth in economic ties between Israel and both countries, highlighting a disconnect between activist discourse and institutional decision-making grounded in rationalist, cost-benefit logic. The thesis concludes that the BDS movement’s ideological assumptions are largely incompatible with prevailing economic and political realities in the EU and selected member states.
Vedoucí práce: Jaroslav Weinfurter
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses